Influencia de la lactancia materna y su relación con la desnutrición infantil en los niños menores de 2 años en el Centro de Salud Enrique Ponce Luque, Babahoyo, 2015 - Sevilla Ruiz, Mercedes Rocío (2015)
The research work is framed in 7 chapters that refer to the issues raised, as in Ecuador breastfeeding is widespread, starting in 96.7% of newborns; however there is a high rate of giving it for various reasons, thus depriving their children of a food with a nutritional superiority. The nutritional status of infants and young children, is part of the broader problems of poverty, lack of resources, social injustice and environmental degradation. The weaning period is a critical step that often leads to malnutrition and disease, when the child does not receive an adequate diet, both in quantity and quality, hygienically prepared and acceptable from all points of view: cultural, social, economic, etc. Chapter I, makes a summary of the issues raised justifies research raises objectives concluding with assumptions and variables to investigate, Chapter II develops the theoretical framework of the research, basing the concept and legal basis of the issue, Chapter III determines the proposed methodology, the chapter IV Graphical and analyzes the results of surveys of 41 mothers of children under two years attending the Health Center Enrique Ponce Luque, Chapter V describes the conclusions and recommendations the issues raised, the sixth chapter details of literature used as a tool to obtain the scientific basis of the subject and the last chapter VII annexed evidence made in the research process. Keywords. - Breastfeeding - Child malnutrition - Ecuador - Health care facilities - Influences